2018
DOI: 10.1109/tcbb.2018.2812189
|View full text |Cite
|
Sign up to set email alerts
|

ANTENNA, a Multi-Rank, Multi-Layered Recommender System for Inferring Reliable Drug-Gene-Disease Associations: Repurposing Diazoxide as a Targeted Anti-Cancer Therapy

Abstract: Existing drug discovery process follows a reductionist model of "one-drug-one-gene-one-disease," which is inadequate to tackle complex diseases involving multiple malfunctioned genes. The availability of big omics data offers opportunities to transform drug discovery process into a new paradigm of systems pharmacology that focuses on designing drugs to target molecular interaction networks instead of a single gene. Here, we develop a reliable multi-rank, multi-layered recommender system, ANTENNA, to mine large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…We proposed a list of described mammalian QRs with reported Km values, the name and structure of the specific inhibitors available for these enzymes, and the IC50 value reported for cancer cells as potential targets to inhibit to promote ferroptosis in conjunction with GPX4 inhibitors (Table 3). 0.87 [226] when the substrate is lipid hydroperoxides. Other QRs, with similar or higher Km values for quinones, are also putative targets for cancer treatment combined with GPX4 inhibitors.…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
“…We proposed a list of described mammalian QRs with reported Km values, the name and structure of the specific inhibitors available for these enzymes, and the IC50 value reported for cancer cells as potential targets to inhibit to promote ferroptosis in conjunction with GPX4 inhibitors (Table 3). 0.87 [226] when the substrate is lipid hydroperoxides. Other QRs, with similar or higher Km values for quinones, are also putative targets for cancer treatment combined with GPX4 inhibitors.…”
Section: The Future Of Nanoparticles (Np) For Cancer Targeting and Timentioning
confidence: 99%
“…In a comprehensive benchmarking study, ANTENNA outperformed the more conventional OCCF methods. Using ANTENNA, Wang et al showed that diazoxide might inhibit the growth of triple negative breast cancer (TNBC) cells efficiently (Wang et al, 2018). Lim et al applied FASCINATE to a three-layered drug-gene-side effect network model to identify biological pathways associated with rare side effects.…”
Section: Application Of Hmln In Omics Data Integration and Analysismentioning
confidence: 99%
“…3D-REMAP not only is scalable to tens of thousands of protein targets on a genome scale but also takes the uncertainty of observed or inferred drug-target interactions into consideration, and consolidate their consistency or conflict relations in a global context. Thus, it may predict offtargets that are missed by the protein structure-based approach and other chemoinformatics methods [26,34].…”
Section: Protein Kinases Are Predicted To Be the Off-target Of Pde3 Imentioning
confidence: 99%